The Application of Scientific Approach Based on Learning Community Using Corners of Information to Improve The Cooperation and Learning Achievement on Additives and Addictives Substances at Grade VIIIE SMP Negeri 22 Surakarta Academic Year 2014/2015 - Herni Budiati (Universitas Sebelas Maret, 2015)
The aim of this research is to improve the cooperation and the learning achievement on additives and addictives substances of VIIIE graders of SMP Negeri 22 Surakarta in academic year 2014/2015 through the application of scientific approach based on learning community using corners of information.The research was Classroom Action Research wich held in SMP Negeri 22 Surakarta in 1stsemester academic year 2014/2015. The research subjects were 31 VIIIE graders of SMP negeri 22 Surakarta. The topic learnt in this research was additives and addictives substances. Data was collected by observing the learning process and testing the understanding of students. The instruments of the research consisted of lesson plans, observation sheet of core competency 2 (social attitudes) which included responsibility and cooperation attitude, blue print and tests as an assesment of core competency 3 (knowledge competency), and guidelines for core competency 4 assesment (skills competency). The procedures in this classroom action research used the Kemmis and Taggart model which consists of plan, action, observation, and reflection. Data were analyzed by descriptive qualitative.The research showed an increase of cooperation skills and learning achievement of additives and addictives substances subject in class VIIIE SMP Negeri 22 Surakarta academic year 2014/2015 through the application of scientific approach by learning community using corners of information. Keywords: Scientific Approach, Learning Community, Corners of Information, Cooperation